Generalized Regression Neural Network for Prediction of Peak Outflow from Dam Breach - Sammen S.S.; Mohamed T.A.; Ghazali A.H.; El-Shafie A.H.; Sidek L.M. (Springer Netherlands, 2023)
Dams; Digital storage; Disasters; Failure (mechanical); Mean square error; Neural networks; Regression analysis; Breach outflow; Dam failure; Dam safety; Generalized regression artificial neural networks; Generalized regression neural networks; Reservoir characteristic; Root mean square errors; Training and testing; Reservoirs (water); artificial neural network; dam failure; flow field; outflow; peak discharge; peak flow; prediction; regression analysis; smoothing